Development of computational method to determine maximum void ratio of sand-soil particles using gravitational sphere packing method - Roozbahani, Mohammad Mahdi (2012)
These days, there has been an increasing interest in virtual reality simulation of the geotechnical field. More recently, literature has emerged that offers linear experimental Equation which positively correlates the maximum and minimum void ratio of sandy-soil particles. However, far too little attention has been paid to virtually simulate one of this parameter in order to rapidly compute these main parameters of the relative density without any need to do experimental works. Gravitational sphere packing which arranges non-overlapping spheres within a confined space has powerful capability to simulate the interaction of large number of particles. The goal of this research is to employ gravitational sphere packing to compute maximum void ratio of sandy-soil particles with particle size distribution as input data. In this study, pre-processing, processing, and post-processing codes of the optimized gravitational sphere packing were developed in MATLAB software. In pre-processing stage, the initial position of the spheres was determined in (x-y) plane by applying different random number distributions. At the stage of processing, three manners of rolling, collision, and stability conditions were considered to pack particles for each incoming sphere within the cylindrical container. The post-process code computes porosity of packed particles through the cylindrical container for both with and without boundary effects. The simulated model was validated by ASTM D 4254 standard method for measuring the maximum void ratio in metal cylindrical container, in which soil particles with different types of sorting are employed for comparison. Results showed that maximum void ratio of dry sandy-soil particles was computed by considering wall-sphere interaction condition in gravitational sphere packing. However, deactivation of boundary effects led to calculate the porosity of the unconsolidated wet sandy-soil particles. Both above mentioned results had close values in agreement with the experimental works. The study also revealed that log-normally particle size distribution provides the lowest value of the porosity. In addition, particles had high potential to be packed in square container with the lowest value of the porosity. All in all, the new presented method of optimized gravitational sphere packing rapidly simulates arrangement of the soil particles in dilute suspension. The rapid code implementation of this method can compute the main parameters of the relative density with high accuracy which was verified by ASTM D 4254 standard test.